The future of ISIS : regional and international implications - Al-Istrabadi, Feisal; Ganguly, Sumit (Brookings Institution, 2018)
"Examines how the terrorist group the Islamic State (known also in the West as ISIS or ISIL) will affect not only the Middle East but the global order and what the global community can do to counter its influence"--Provided by the publisher.